Injection-Site Sarcoma in a Dog: Clinical and Pathological Findings. (9th May 2017) - Jacobs, Terry M.; Poehlmann, Cathy E.; Kiupel, Matti
Abstract : This case report documents the clinical and pathological findings in a dog that rapidly developed a high-grade sarcoma at the site of multiple vaccinations and follows the response to surgery and adjunct treatment with toceranib. An 11-year-old female spayed Labrador Retriever presented with dorsocervical subcutaneous masses at the injection site three weeks after receiving DA2 PP-Lepto, Rabies, and Bordetella vaccinations. A high-grade soft tissue sarcoma was diagnosed microscopically and immunohistochemistry revealed positive expression of VEGFr, PDGFr, SCF, and EGFR. Repeat surgical resections and targeted treatment with toceranib resulted in a stable remission for nearly two years.